Birth outcomes after exposure to mebendazole and pyrvinium during pregnancy – A Danish nationwide cohort study. (16th November 2016) - Torp-Pedersen, Arendse; Jimenez-Solem, Espen; Cejvanovic, Vanja; Poulsen, Henrik Enghusen; Andersen, Jon T.
Abstract: Mebendazole and pyrvinium are anthelmintics used to treat infections with pinworms, a common infection in children. Other indications for treatment with mebendazole are infections with soil-transmitted helminths. These infections are rare in Denmark, but affect more than 1.5 billion people worldwide. Limited safety data of anthelmintics during pregnancy exists and the purpose of this study was to investigate the association between exposure to mebendazole or pyrvinium during pregnancy and the adverse pregnancy outcomes: congenital malformations, stillbirths, neonatal mortality and small for gestational age. The Danish Fertility Database was used to identify all births in Denmark from 1997 to 2007. Maternal exposure to anthelmintics was identified through The Danish Prescription Registry. Of 713667 births, 2567 mothers redeemed a prescription for mebendazole; 1588 for pyrvinium. Logistic regression analysis adjusted for potential confounders. We found no association between exposure to mebendazole and major congenital malformations (OR = 0.7 (CI 95% 0.5–1.1)) or other negative birth outcomes and we found no association between exposure to pyrvinium and major congenital malformations (OR = 0.8 (CI 95% 0.4–1.5)) or other negative birth outcomes. No increased risk was found of having negative birth outcomes after exposure at any trimester during pregnancy.